A Class of Exponential Estimator to Estimate the Population Mean in the Presence of Non-Response - Dansawad, Napattchan (Naresuan University Journal: Science and Technology (NUJST), 2019)
This paper presents a class of exponential estimator to estimate the population mean in the presence of non-response using a small amount of known auxiliary information, when non-response occurs only on the study variable. Furthermore, the study also proposes a modified exponential estimator using a linear combination of a few members of the proposed class. Properties of the proposed estimators are obtained up to first order approximation. Results from theoretical and empirical studies have shown that the proposed modified exponential estimator at its optimum performs more efficient than all other relevant estimators.   Keywords: Exponential estimator, Study variable, Auxiliary variable, Non-response